HUBUNGAN SELF EFFICACY DENGAN STRES PADA MAHASISWA FAKULTAS KEPERAWATAN UNIVERSITAS RIAU DALAM MENYUSUN SKRIPSI DI MASA PANDEMI COVID-19 - Syintya Eka Putri; Jumaini Jumaini; Sri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Students in the process of working on a thesis are often faced with various problems that can cause stress. Students may have high self-efficacy to turn obstacles into challenges so that students don't just give up in the face of obstacles in writing a thesis. Determine the relationship between self-disclosure and self-efficacy with stress during the Covid-19 pandemic. Using descriptive correlation design, cross sectional approach. The research sample was 129 people using total sampling technique. The analysis used is univariate analysis and bivariate analysis using chi-square test. The results of the bivariate test have no relationship between self-disclosure and stress in students (p value 0.589 > = 0.05) and there is a significant relationship between self-efficacy and stress in students (p value 0.001 < = 0.05). There is no relationship between self-disclosure and stress and there is a relationship between self-efficacy and stress for studentsKeywords: self efficacy, stress, students